2019
DOI: 10.1073/pnas.1819660116
|View full text |Cite
|
Sign up to set email alerts
|

bHLH-PAS protein RITMO1 regulates diel biological rhythms in the marine diatom Phaeodactylum tricornutum

Abstract: Periodic light–dark cycles govern the timing of basic biological processes in organisms inhabiting land as well as the sea, where life evolved. Although prominent marine phytoplanktonic organisms such as diatoms show robust diel rhythms, the mechanisms regulating these processes are still obscure. By characterizing aPhaeodactylum tricornutumbHLH-PAS nuclear protein, hereby named RITMO1, we shed light on the regulation of the daily life of diatoms. Alteration of RITMO1 expression levels and timing by ectopic ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 38 publications
(71 reference statements)
5
55
0
1
Order By: Relevance
“…Overall, the studied bZIP transcription factors like PtbZIP10 and PtbZIP18 revealed a rather high transcript abundance. PtbHLH1a (RITMO1), which recently has been shown to be involved in the circadian regulation of P. tricornutum ( Annunziata et al., 2019 ), is strongly transcribed after 10 min, and to a lesser extent after 60 min, which is mirrored much weaker in the mutant lines. Interestingly, PtbHLH1b, which is related to RITMO1, shows a very similar but even more pronounced expression pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the studied bZIP transcription factors like PtbZIP10 and PtbZIP18 revealed a rather high transcript abundance. PtbHLH1a (RITMO1), which recently has been shown to be involved in the circadian regulation of P. tricornutum ( Annunziata et al., 2019 ), is strongly transcribed after 10 min, and to a lesser extent after 60 min, which is mirrored much weaker in the mutant lines. Interestingly, PtbHLH1b, which is related to RITMO1, shows a very similar but even more pronounced expression pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that the light acclimation ability in diatoms instead is strongly dependent on the aureochrome photoreceptor system ( Schellenberger Costa et al., 2013 ), which is lacking in the green lineage. PtbHLH1a (also called RITMO1) is involved in regulation of circadian rhythm of diatoms ( Annunziata et al., 2019 ). Transcription of RITMO1 in our experiment is increased by about 30-fold upon blue light exposure for 10 min, suggesting that its rhythmicity might be triggered by activation of aureochromes and/or other photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that N. spartinetensis shows a much smaller size than G. fasciola, and probably a different migratory behavior (see Underwood et al, 2005) is an additional asset. The complementary use of the epipelic model Seminavis robusta (Blommaert et al, 2017(Blommaert et al, , 2018, which genome has been sequenced, will allow to search for molecular players, such as timekeepers (Annunziataa et al, 2019), photoreceptors (Jaubert et al, 2017), and diurnal-responsive genes (see Meyer et al, 2003;Blommaert et al, 2020), of the rhythmic migratory light-tuned response of intertidal epipelic MPB. JL performed samples and data analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The endogenously controlled rhythmic MPB migration, modeled onto intertidal flat environmental conditions, would allow MPB to perform surface and depth biological processes in the most optimal conditions. Although endogenous circadian clocks, their components and regulation, have been well detailed in several algal lineages, they remain uncharacterized in diatoms (Noordally and Millar, 2015), with the exception of the recent discovery of a time-keeping molecular component, which controls the diel rhythmic expression of many genes (Annunziataa et al, 2019).…”
Section: Monitoring Of the Changes In The Mpb Pab At The Surface Of Smentioning
confidence: 99%
“…A total of 188 candidates, from 18 TF families (HSF, Myb, Zn_finger_C2H2, bZIP, Zn_finger_CCCH, bHLH, Sigma-70, Zn_finger_TAZ, CBF/NF, E2F-DP, CSF, Aureochrome, TRF, CCAAT-binding, AP2-EREBP, TAF9, CXC, Homeobox) corresponded to genes assigned to a PhaeoNet merged module ( Figure 5 and Supplementary Table 4). Given that the regulation of gene expression by transcription factors play a key role in the growth and progression of the cell cycle, the distribution within merged modules genes implicated in the cell cycle (cyclins) and in light perception events (e.g., phytochrome, cryptochrome) were additionally investigated, as well as genes implied in transcription and histone-related processes ( Figure 5 and Supplementary Table 4; Huysman et al, 2013;Annunziata et al, 2019).…”
Section: Biological Interpretation Of Merged Modulesmentioning
confidence: 99%